The affective experience of handling digital fabrics: Tactile and visual cross-modal effects - Wu, D.; Wu, T.; Singh, H.; Padilla, S.; Atkinson, Doug; Bianchi-Berthouze, N.; Chantler, M.; Baurley, S. (2011)
In the textile sector, emotions are often associated with both physical touch and manipulation of the product. Thus there is the need to recreate the affective experiences of touching and interacting with fabrics using commonly available internet technology. New digital interactive representations of fabrics simulating handling have been proposed with the idea of bringing the digital experience of fabrics closer to the reality. This study evaluates the contribution of handling real fabrics to viewing digital interactive animations of said fabrics and vice versa. A combination of self-report and physiological measures was used. Results showed that having previous physical handling experience of the fabrics significantly increased pleasure and engagement in the visual experience of the digital handling of the same fabrics. Two factors mediated these experiences: gender and interoceptive awareness. Significant results were not found for the opposite condition.